2009
DOI: 10.1177/0883073809333526
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Seizure Activity in a Human Neonate Treated With Bumetanide, an Inhibitor of the Na+-K+-2Cl- Cotransporter NKCC1

Abstract: Neonatal seizures have devastating consequences for brain development and are inadequately treated by available antiepileptics. In neonates, gamma-aminobutyric acid (GABA) is an excitatory neurotransmitter due to elevated levels of intraneuronal chloride achieved by robust activity of the Na(+)-K(+)-2Cl( -) cotransporter (NKCC1). This depolarizing action of GABA likely contributes to the lowered seizure threshold, increased seizure propensity, and poor efficacy of GABAergic anticonvulsants among infants. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 26 publications
1
72
0
2
Order By: Relevance
“…In line with this view, it has been reported that antiepileptic drugs such as topiramate inhibit the cytosolic carbonic anhydrase (Dodgson et al, 2000) thus decreasing or abolishing GABA A receptor-mediated depolarizing responses (Herrero et al, 2002). In addition, it has been proposed that inhibiting NKCC1 with bumetanide can reduce and even abolish seizures in rodent models of neonatal seizures (Dzhala et al, 2005(Dzhala et al, , 2010Nardou et al, 2009) and in human neonates (Kahle et al, 2009). NKCC1, which increases intracellular Cl − , is elevated in neonates where GABA A receptor-mediated conductances are mainly excitatory.…”
Section: Gaba a Receptor-mediated Depolarizing Actionsmentioning
confidence: 88%
“…In line with this view, it has been reported that antiepileptic drugs such as topiramate inhibit the cytosolic carbonic anhydrase (Dodgson et al, 2000) thus decreasing or abolishing GABA A receptor-mediated depolarizing responses (Herrero et al, 2002). In addition, it has been proposed that inhibiting NKCC1 with bumetanide can reduce and even abolish seizures in rodent models of neonatal seizures (Dzhala et al, 2005(Dzhala et al, , 2010Nardou et al, 2009) and in human neonates (Kahle et al, 2009). NKCC1, which increases intracellular Cl − , is elevated in neonates where GABA A receptor-mediated conductances are mainly excitatory.…”
Section: Gaba a Receptor-mediated Depolarizing Actionsmentioning
confidence: 88%
“…One example of this is targeting NKCC1, which accumulates Cl 2 in glioma cells and is important for migration [11]. Its inhibitor, bumetanide, is already approved by the FDA as a loop diuretic and is currently also being tested to treat neonatal seizures [63].…”
Section: Therapymentioning
confidence: 99%
“…[11] Bu durum, bu AEİ'lerin et- Hedef değişiklikleri metanidin insanlarda da antiepileptik etki gösterebileceğini düşündürmektedir. [23] Barbitürat ve benzodiazepin benzeri GABA agonistleri, olgunlaşmış nöronlarda, GABA reseptör ilişkili klorid kanallarının açılma süresini ve/veya sıklığını artırarak hücre içi klor düzeyinin artmasına neden olurlar. Dolayısıyla GABA elektrokimyasal gradyantle uyumlu olarak klorun pasif içe akımını, membran hiperpolarizasyonunu ve potansiyel nö-ronal inhibisyonu tetikleyerek nöbet aktivitesini düşürür.…”
Section: Hedef (Target) Hipoteziunclassified
“…[24] Eş taşıyıcının fonksiyonunu inhibe eden ilaçlar ile GABA'nın hiperpolarizasyon görevini yapmasını veya yeniden yapılanmasını sağlayabilecek klinik çalışmalar öngörülebilir. [23] Diğer hedefler, vigabatrin tarafından inhibe edilen GABA transaminaz, asetazolamid tarafından inhibe edilen karbonik anhidraz enzimleri ve levetirasetam bağlanma bölgesi olan sinaptik vezikül protein SV2A'dır. SE sonrası sıçanlarda ve hipokampal sklerozlu hasta dokularında levetirasetamın bağlandığı bölge olan SV2A'da belirgin değişiklikler göste-rilmiştir.…”
Section: Hedef (Target) Hipoteziunclassified